Maternal attachment and cognitive functioning of children in institutionalized care in Malaysia: variation by sex - Syed Mustafa, Siti Zakiah (2014)
Children maltreatment is becoming an issue in Malaysia due to the increasing number of cases reported every year. Institutionalized children are often those who are maltreated in terms of abuse and neglect particularly by their parents. The present study aims to determine the extent to which maternal attachment (MA) influences institutionalized children cognitive functioning (CF). Additionally, the study examined whether the relationship varies across sex.Sample comprised 257 children (mean age: 10 year) in institutionalized care in selected states in Malaysia. The Malay version of Inventory for Peer and Parent Attachment-revised (IPPA-Malay Children) parent scale was used to measure retrospective MA, while CF was assessed using Raven’s Colored Progressive Matrices (R-CPM).Data were collected using semi-structured technique at the respective institutions. At the bivariate level, children who reported to experience better attachment with their mothers demonstrated higher levels of CF.Hybrid model analysis using SEM showed that the relationship between MA and CF is stable across sex of child.The study concludes that MA significantly influences the CF of children residing in institutionalized care. Sex of child is not a significant moderator in the relationship. Findings imply the important role of attachment to a significant other in fostering the CF of children.Findings might be useful to those involve in prevention and intervention programs related to cognitive development of children in institutions.